The Effect Of Company Size, Financial Distress, And Accounting Conservatism On Tax Avoidance: (Empirical Study on Property & Real Estate Sector Companies On The Indonesia Stock Exchange 2018-2022) - Apriliana, Tiara; Margie, Lyandra Aisyah (Journal of Industrial Engineering & Management Research, 2024)
This study was conducted to analyze the effect of company size, financial distress and accounting conservatism on tax avoidance. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange in 2018-2022. The technique used is panel data regression. The sample selection was carried out using purposive sampling method from secondary data in the form of financial statements and found as many as 13 sample companies with 5 years of observation, so that the total sample in this study was 65 company year data. Hypothesis testing is done using the Eviews 12 application. Based on the results of Eviews 12 testing, it is found that simultaneously company size, financial distress and accounting conservatism have a significant effect on tax avoidance. While partially, only accounting conservatism has a significant effect on tax avoidance. while company size and financial distress variables have no significant effect on tax avoidance.